Developmental defect of email in children and adolescent: a review - Vera YULINA; Meirina GARTIKA (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Developmental defect of enamel (DDE) is a defect on the surface of the enamel layer thatoccurs during tooth development due to various genetic and environmental factors. Defects that occurresult in changes in color and texture on the enamel surface so that it interferes with aesthetics. Thedefect level that happens can be classified based on the DDE index to determine the option of a casetreatment plan consisting of enamel microabrasion, conservative aesthetic restoration, and bleaching.This review aims to analyze and review studies related to DDE in primary and permanent teeth. Anelectronic search was conducted through PubMed/Medline, Google Scholar, Semantic Scholar,SpringerLink, and Wiley Online Library using the keywords defect email, developmental defectemail, and defect on primary teeth for research published between January 2011 and April 2020, thesame article was eliminated, the initial search resulted in a total of 55 articles. The exclusion of articleswas carried out based on the title and abstract so that finally, 45 relevant articles were obtained. Threestudies were included in this review for qualitative analysis. The results show that Enamel (DDE)Developmental defects can occur in both primary and permanent teeth with the same prevalence rate. KEYWORDS: Developmental Defect of Email (DDE), DDE Index, defect to primary teeth, defect topermanent teeth